Tanggung Jawab Notaris Dalam Legalisasi Dokumen Warga Negara Asing Menurut Konvensi Apostille - Nanda, Reza Ria; Velentina, Rouli Anita (JURNAL USM LAW REVIEW, 2022)
The purpose of this paper is to analyze the policy of the Apostille Convention in Indonesia and the responsibilities of a notary in the document legalization process. A simpler legalization process with less time and cost is comprehensively regulated in The Hague Convention Abolishing the Requirements for Legalization for Foreign Public Documents 1961 (Apostille Convention). A notary is a public official who is authorized to make deeds and other authorities. The duties and work of a notary are not only to make authentic deeds but also to register and ratify underhanded deeds, namely legalization and waarmerking efforts. Notaries have a role in the Apostille Convention which has been accessed by Indonesia as a public official who legalizes every deed legalized by the parties. This study questions the legalization of foreign public documents in Indonesia after the Apostille Convention comes into effect and the legal responsibilities of a notary in the document legalization process after the Apostille Convention comes into effect in Indonesia. The conclusion of this study is that the Apostille Convention aims to simplify the authentication of public documents to be used abroad by removing the requirements for legalization, which is often time-consuming and expensive and still requires the role of an authorized notary in legalizing foreign public documents. Tujuan dari tulisan ini untuk menganalisis kebijakan Konvensi Apostille di Indonesia dan tanggung jawab Notaris dalam proses legalisasi dokumen. Proses legalisasi yang lebih sederhana dengan waktu dan biaya yang tidak begitu banyak, diatur secara komprehensif dalam The Hague Convention Abolishing the Requirement for Legalisation for Foreign Public Documents 1961 (Apostille Convention). Notaris adalah pejabat umum yang berwenang dalam membuat akta dan kewenangan lainnya. Tugas dan pekerjaan dari seorang Notaris tidak hanya membuat akta autentik, akan tetapi juga melakukan pendaftaran dan mengesahkan akta-akta yang dibuat dibawah tangan yaitu upaya legalisasi dan waarmerking. Notaris mempunyai peran dalam Konvensi Apostille yang telah diaksesi oleh Indonesia sebagai pejabat umum yang melegalisasi setiap akta yang dilegalisasi oleh para pihak. Penelitian ini mempertanyakan legalisasi dokumen publik asing di Indonesia setelah keberlakuan Apostille Convention dan tanggung jawab hukum Notaris dalam proses legalisasi dokumen setelah keberlakuan Apostille Convention di Indonesia. Kesimpulan dari penelitian ini adalah Konvensi Apostille bertujuan menyederhanakan autentikasi dokumen publik yang akan digunakan di luar negeri dengan menghapus persyaratan untuk legalisasi, yang seringkali memakan waktu dan mahal serta tetap membutuhkan peranan Notaris yang berwenang dalam melegalisasi dokumen publik asing.